Methylation on RNA: A Potential Mechanism Related to Immune Priming within But Not across Generations - Castro-Vargas, Cynthia; Linares-López, César; López-Torres, Adolfo; Wrobel, Katarzyna; Torres-Guzmán, Juan C.; Hernández, Gloria A. G.; Wrobel, Kazimierz; Lanz-Mendoza, Humberto; Contreras-Garduño, Jorge (Frontiers in Microbiology, 2017)
Invertebrate immune priming is a growing field in immunology. This phenomenon refers to the ability of invertebrates to generate a more vigorous immune response to a second encounter with a specific pathogen and can occur within and across generations. Although the precise mechanism has not been elucidated, it has been suggested that methylation of DNA is a cornerstone for this phenomenon. Here, using a novel method of analytical chemistry (a reversed-phase liquid chromatography procedure) and the beetle Tenebrio molitor as a model system, we did not find evidence to support this hypothesis taking into account the percentage of methylated cytosine entities in DNA (5mdC) within or across generations. However, we found a lower percentage of methylated cytosine entities in RNA (5mC) within but not across generations in immune priming experiments with adults against the bacteria Micrococcus lysodeikticus and larvae against the fungus Metarhizium anisopliae. To our knowledge, this is the first report suggesting a role of differential methylation on RNA during immune priming within generations.